The Conservation Value of Small Fragments For Atlantic Forest Reptiles. (18th January 2016) - Lion, Marília B.; Garda, Adrian A.; Santana, Diego J.; Fonseca, Carlos Roberto
Abstract: Loss and fragmentation of natural habitats are key contributors to the decline of populations and impoverishment of biological communities. The response to these disturbances can vary substantially among taxa and depends on spatial metrics of habitat fragments and the surrounding landscape. Herein we test how fragment area, shape, isolation, and matrix quality affect reptile richness, abundance, and occurrence in Brazilian Atlantic Forest fragments, a biodiversity hotspot with a poorly studied reptile fauna. We used 23 forest fragments, ranging from 2 to 30 hectares, surrounded by different matrix types, including sugarcane crop fields, cattle ranching, subsistence farmlands and rural communities. Species richness, total reptile abundance, population abundance, and occurrence probability of many species decreased with fragment area. Model selection suggested that fragment area is the main predictor of both richness and abundance, but matrix quality as well as fragment shape are also important predictors. For population abundance and occurrence probability, fragment area and proximity were the most important predictors followed by fragment shape and matrix quality, but the strength and even the sign of predictors varied substantially among species. We highlight that the value of small fragments should not be neglected for the conservation of Atlantic Forest reptiles.